Optimizing the Sabhara Unit Four-Wheel Patrol in preventing Crime and Theft at the Bandung Police - Sibuea, Toman Febriandi (Advances in Police Science Research Journal, 2024)
The rampant crime of motor vehicle theft is a phenomenon that often occurs in Indonesian society should be a serious concern. The increasing level of crime of fraud in the city of Bandung requires strict handling. The Sabhara Unit is required to carry out its duties and functions professionally. The purpose of this study is to analyze and describe the optimization efforts to streamline the implementation of the Sabhara four-wheeled patrol unit in preventing the number of curanmor in the Bandung Regional Police Legal Area, as well as to find out what factors influence the implementation of the Patrol in preventing the number of curanmor. This type of research is a qualitative research located in the jurisdiction of Bandung Police. Data collection techniques are done by observation, interviews and document studies. Data analysis was performed by data reduction, data presentation and conclusion drawing. To optimize the implementation of the Sabhara Four Wheel Patrol unit in preventing the theft of motor vehicle theft, Kasat Sabhara has an innovation or new breakthrough to support the activities of the Four Wheel Patrol called the Strong Point. Internal factors that support the complete number of members owned by the Sabhara Unit while the inhibiting factor is the small number of handy talk (HT) communication tools. External factors that influence are the weather that is not supportive, traffic conditions and also the people who are lacking to participate. The results found that the implementation of Sabhara Polrestabes Bandung's four-wheeled patrol unit had referred to the latest regulations. However, in terms of several aspects such as stages, time of patrols, and targets of patrols, it was considered not optimal in preventing vehicle theft that occurred.